EFEKTIVITAS DISKRESI KEPOLISIN MELALUI PENDEKATAN RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA DI KOTA BATAM (STUDI KASUS POLRESTA BARELANG) - Manik, Doni Sugara; Husna, Lenny (LPPM Universitas Putera Batam, 2023)
The formation of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT) which is oneof the government's supports to eliminate all forms of violence as a form of crime of Domestic Violence (KDRT)can be subject to sanctions such as imprisonment or confinement. In this case the Effectiveness of PoliceDiscretion through the application of Restorative Justice in criminal acts of domestic violence. Based on LawNumber 2 of 2002 concerning the Indonesian National Police in article 18 paragraph 1 related to police discretionwhich reads For the public interest officials of the Indonesian National Police in carrying out their duties andauthorities can act according to their own judgment. So in this case the police explained that for police discretionin terms of restorative justice the effectiveness here is to reduce the high rate of divorce and the existence of thisRestorative justice is applied to restore the situation to how it was before and to provide a deterrent effect forperpetrators not to repeat it. With the existence of restorative justice, the police also stated that 80% had adeterrent effect on the perpetrators and 20% had repeated crimes due to light hands or economic aspects.